Impact of spatial rainfall resolution on point-source solute transport modelling. Issue 16 (10th December 2017) - Selim, Tarek; Persson, Magnus; Olsson, Jonas
ABSTRACT: Numerical simulations of unsaturated solute transport from point sources were carried out using HYDRUS-1D. Three different soil types cropped with spring wheat were considered at three different locations in Sweden: Malmö, Norrköping and Petisträsk. Two types of rainfall data were used, point-scale raingauge measurements and a gauge-adjusted weather radar product at four spatial resolutions, 2 × 2, 6 × 6, 10 × 10 and 14 × 14 km 2 . The results showed that differences in the mean solute transport depths were small and not significant, with the exception of Petisträsk. Maximum transport depths were in most cases significantly larger using raingauge data compared to radar data. The results showed that using areal-averaged rainfall input will give solute transport estimations close to those using point-measured data. This shows the great potential in using radar-measured rainfall data in small-scale hydrological applications.